A drop in the ocean: Monitoring fish communities in spawning areas using environmental DNA. Issue 1 (30th April 2020) - Ratcliffe, Frances C.; Uren Webster, Tamsyn M.; Garcia de Leaniz, Carlos; Consuegra, Sofia
Abstract: Early life stages of aquatic organisms are particularly vulnerable to climatic stressors; however, they are difficult to monitor due to challenges in sampling and morphological identification. Environmental DNA (eDNA) from water samples represents an opportunity for rapid, nondestructive monitoring of aquatic community composition as well as single species monitoring. eDNA can also detect spawning events, although has not been yet tested in offshore spawning grounds. Here, we used metabarcoding of water samples to detect the presence of key fish taxa in spawning areas that are difficult to monitor using traditional means. We analyzed DNA from water samples and fish larvae samples at 14 offshore sites, using 12S mitochondrial metabarcoding and compared taxa detections, diversity, and community structure estimated by both sample types. Species richness and diversity did not differ between water and larvae samples. Both sample types detected a core of 12 taxa across the survey, with an average agreement in detections of 75% at sampling site level. Water samples detected two of the three most abundant taxa, the sandeel, Ammodytes marinus, and clupeids, Clupea harengus/Sprattus sprattus, at 31% and 38% more sites than larvae samples respectively, while Callionymus sp. was more prevalent in larvae samples. Mackerel ( Scomber scombrus ) and blue whiting ( Micromestius poutassou ) were only detected in water samples despite sampling taking place at peak spawning times for these species. Our results demonstrate that eDNA metabarcoding provides a rapid and feasible monitoring method for the management of key taxa, such as sandeel, that cannot be easily monitored using traditional capture surveys. Abstract : We carried out DNA metabarcoding from fish larvae and water samples simultaneously collected at the same sampling sites to detect the presence of key fish taxa in spawning areas that are difficult to monitor using traditional means. We show that eDNA from water samples not only reflects larval composition accurately, but can also be more sensitive for particular taxa, such as sandeels or herring/sprat.